There is no Small Enemy: A Peripheral Single Penetrating wound by Scissors with Death Results (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
A case of a 78-year-old female is reported, who died from bleeding caused by a small incised cutting wound, located on the right leg and affecting the fibular artery. Some 6 to 7 hours passed after the wound was caused and, all through this time she did several things, among them asking for help. Some first aid knowledge would probably avoid such deaths.
Keywords: Nail scissors stabing; bleeding,; accident